General Public Perceptions towards Medicines in the State of Penang Malaysia - Mahmoud Sa'di Al-Haddad (Archives of Pharmacy Practice, 2012)
Objectives: This study aims to evaluate patients' knowledge,sources of knowledge, and perceptions towards medicines inthe state of Penang, Malaysia.Materials and Methods: A cross sectional study design usingconvenience sampling technique was adopted in this study. Apre-validated questionnaire was developed and distributed to800 participants in the state of Penang, Malaysia. All data wasanalysed using SPSS version 16. A p-value of less than 0.05 wasconsidered significant.Results: 700 respondents successfully responded to thesurvey. One third of the respondents were aware ofconventional/modern medicines. Whereas only 3.3% knewwhat is meant by generic medicines. High proportion ofrespondents wrongly perceived the quality of medicines to berelated to the familiarity with the medicine, frequency ofadvertisements, price, packaging and country of themanufacturer. In addition, friends, family members, financialstatus, and previous history, found to play an important role inpatients decisions when selecting medicines.Conclusion: Results of this study urge for a nationalawareness program to the public regarding medicines.Decision makers have to consider these findings since highproportion of the public perceive and consume medicinesirrationally